Catalytic pyrolysis of biomass with potassium compounds for Co-production of high-quality biofuels and porous carbons. (1st January 2020) - Shen, Yafei; Zhang, Niyu; Zhang, Shu
Abstract: This paper studied the catalytic pyrolysis of rice husk (RH) with different K-compounds (i.e., KOH, K2 CO3, and K2 C2 O4 ) for co-production of biofuels and porous carbons. The decomposition of biomass occurred at lower temperature ranges due to the catalytic performance of K-compounds, following the order of KOH > K2 CO3  > K2 C2 O4 . By fast pyrolysis of RH with the K-compounds, the number of organic compounds was significantly reduced. More hydrocarbons (e.g., benzene, long-chain alkanes) were generated due to the in-situ catalytic upgrading (e.g., deoxygenation) of bio-oil. Pyrolysis of biomass with K-compounds could also accelerate the generation of unsaturated aliphatic hydrocarbons. In particular, pyrolysis of RH with K2 C2 O4 could result in the bio-oil with high-content of hydrocarbons and with low-content of oxygenated compounds (e.g., acids, phenols). Furthermore, the activated char with hierarchically micro-mesoporous structure was applied for toluene sorption. The pristine biochar had a relatively low adsorption time and capacity. By the chemical activation followed by the washing process, the specific surface area (SBET ) of the RH-derived chars was significantly increased. The RHC-K2 C2 O4 had a maximum SBET of 1347 m 2/ g due to its mild activation process, which further contributed to a highest breakthrough time (1230 min) and capacity (609.38 mg/g) on toluene adsorption. Highlights: One-step pyrolysis of biomass with different potassium compounds was studied. The catalytic performance of potassium compounds on biomass decomposition followed the order of KOH > K2 CO3  > K2 C2 O4. Pyrolysis of biomass with K2 C2 O4 resulted in the bio-oil with high-content of hydrocarbons. K2 C2 O4 improved the quality of bio-oil, syngas and biochar compared to KOH. The activated biochar with hierarchically micro-mesoporous structure was beneficial for toluene sorption.